Cyber Marketing Model : Produk UMKM Wilayah Medan-Binjai-Deli Serdang Propinsi Sumatera Utara - Hazmanan Khair; Delyana Rahmawani Pulungan; Linzzy Pratami Putri (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2020)
This study aims to help SMEsowner who are domiciled in Medan, Binjai, and Deli Serdang (MEBIDANG) in expanding the market for products produced by using the website as a more efficient and effective marketing tool for customers. The designing this website using the online shop principle. The problem in this research can be formulated "What is the form of the Cyber Marketing model that will be formulated in the SME product marketing system in MEBIDANG?. This research used the Research and Development (R & D) method, starting from preliminary survey activities, the SME cyber marketing model, testing, socialization and implementation. Data collection techniques by means of field studies, literature studies and literature references and research as support in model development. The result is that with the growth of online businesses, the Indonesian people will get positive benefits in the economy such as welfare growth, new job growth and others. Furthermore, this research will produce a cyber marketing application for SME entrepreneurs in the MEBIDANG area to listing on the Indonesia Stock Exchange. Even so, there are still many SME practitioners who are not interested in using this application to support their business.